O ensino de propriedades periódicas através do lúdico - Zamboni, Geovana (2013)
Due to the importance of using instructional resources in the classroom and of the understanding these are tools to support the teaching, the focus of this research was the creation and evaluation of a didactic game in development of chemical content, involving Periodic Properties. This activity was implemented in E. E. Prof. Marcelo de Mesquita in the city of Ipeúna - SP, with students of two classrooms of Highschool 1st grade. The following step of the research involved: a) the study of Nowadays Chemistry Teaching; b) an investigation of Didactic Resources for Teaching in Brazilian context; c) the teaching of Periodic Properties in Textbooks and Curriculum Proposals of São Paulo State, with the purpose of identify how this content was put to the teachers and also support the development of issues that formed the database of questions used in the game; d) the theoretical study on Didactic Games, to identify what kind of game to develop, and the choice was creating a software. We chose the use of technology in the classroom by creating an electronic game because it presents important instructional possibilities for the Basic Education s teacher. The research was exploratory and its methodology had a qualitative approach to assist in the data collection and its analysis. The instruments for data collection were questionnaires and researcher s observations. The game practice has two parts and one is for diagnostic evaluation. In the diagnostic moment, the students have answered a questionnaire about the Periodic Table and Periodic Properties before the activity and after this played the didactic game itself. Henceforth the students answered another questionnaire about the Periodic Table, its properties and its used resources. By data analysis it was noticed that the game contributed to improve students learning skills, but it s clear that the game is not a self-sufficient tool to teach contents, it must be linked to a sequence of didactic tools, supported by the teacher, considering the pace of pupils' learning and particularity of specific content.